READING TEACHING WITH THE HELP OF SOUND GESTURES FOR PRIMARY SCHOOL CHILDREN WITH MENTAL DEVELOPMENT DISORDERS - Petrova, Daina (Education Reform: Education Content Research and Implementation Problems, 2019)
The native language, its skills, understanding and sense are important to every member of society, it puts thinking, communicating, and text creating into order, and it indicates to educatedness. Literacy as a key skill in everyday life is essential for acquiring and implementing the nowadays’ life skills.There are situations where pupils have not yet acquired reading skills for several years, and the issue becomes topical on how to teach to read in their age and form group, and at different levels of psychological development. One of the options is to start intensive reading learning with the help of sound gestures, where each sound or letter is represented by a gesture. This approach allows pupils starting to read and understand what they read.The purpose of the study is to research the literature on reading learning possibilities and to develop didactic materials for reading teaching with the help of sound gestures for the primary school children with mental development disorders.Study methods: literature analysis, document study, observations, questionnaire, data collection and statistical processing.Based on theoretical knowledge and analysis of literature, the author of the paper has developed didactic materials for reading teaching with the help of the sound gestures for the primary school children with mental development disabilities. Taking into account the principles of special pedagogy and speech therapy, the process of reading teaching with the help of sound gestures focuses on the difficulty levels during reading, deliberate avoidance of difficulties.The research includes the seven primary school children with mental development disorders and three teachers from the mentioned school, 30 respondents from different educational institutions.At the conclusion of the research, evaluating the effectiveness of the didactic material developed, it was concluded that it is possible to contribute to reading teaching through sound gestures for the primary school age children with mental development disorders.